Analysis On The Effectiveness Of “Unbundling” And “Open Access” In Indonesian Gas Business Sector - Aritonang, Parulian Paidi (UI Scholars Hub, 2019)
Natural gas is a very important non-renewable natural resource that controls the lives of many people. Therefore, the exploitation and utilization of natural gas must be carried out wisely and for the greatest prosperity of the people. This is mandated in Article 33 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia that